Jojo's bizarre adventure. Part 7, Steel ball run. Volume 3 - Araki, Hirohiko, 1960- (Steel Ball Run., 2025)
Gyro and Johnny are heading up the front of the pack in the Steel Ball Run race! But just as they're about to reach the finish line, they're attacked yet again. And to make matters worse, when Gyro and Johnny finally uncover the reason behind these constant attacks, they start to realize that the true purpose of the Steel Ball Run is much more sinister than either of them could have ever imagined.